Effects of Gender-Specific Differences, Inflammatory Response, and Genetic Variation on the Associations Among Depressive Symptoms and the Risk of Major Adverse Coronary Events in Patients With Acute Coronary Syndrome. Issue 2 (March 2018) - Sanner, Jennifer; Grove, Megan L.; Yu, Erica; Moeller, F. Gerard; Cron, Stanley G.; Boerwinkle, Eric; Morrison, Alanna C.; Frazier, Lorraine
Depressive symptoms independently contribute to major adverse coronary events (MACEs), with the biological immune response to depression being a likely mediator of this relationship. To determine whether genetic- and/or gender-specific phenotypic differences contribute to associations among depressive symptoms, inflammatory response, and risk of MACE in patients with acute coronary syndrome (ACS), we conducted a prospective study of 1, 117 ACS patients to test a gender-specific model in which depressive symptoms (Beck Depression Inventory-II [BDI-II]) are associated with risk of MACE. Cox proportional hazards models were used to model time to incident MACE and determine whether single-nucleotide polymorphisms (SNPs) in specific inflammatory protein-coding genes and depressive symptoms interact to influence levels of inflammatory proteins or risk of MACE. Females had significantly higher high-sensitivity C-reactive protein and monocyte chemoattractant protein-1 levels. Depression status differed by gender (29.9% of females and 21.1% of males had BDI-II scores indicative of depression [ p = .0014]). Depressive symptoms were associated with MACE; however, the interaction between these symptoms and gender was not significant. SNPs and depressive symptoms did not interact to influence inflammation or MACE. More females than males had BDI-II scores indicative of depression, yet the association between positive depressive symptom status and MACE did not vary by gender. Nor did the SNPs interact with depressive symptoms to influence inflammation or MACE. It remains of interest to identify a high-risk subgroup of ACS patients with genetic polymorphisms that result in immunoinflammatory dysregulation in the presence of depressive symptoms.